Roadmap to high-quality dual Vocational Education and Training - Euler, Dieter [Verfasser] (Bertelsmann Stiftung, 2023)
„The success of Germany’s dual education and training system is viewed worldwide as an example to follow. But how can other countries effectively transfer the model to their national contexts? Prof. Dr. Dieter Euler expores this question in a new study in which he identifies 11 components of the dual system and examines the extent to which each is transferable in various stages of implementation. Emphasizing operational considerations in implementation, his approach shows how individual elements can be transferred and adapted to the uniques conditions of a country.“ (editor; BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; I 1 Internationale Berufsbildung; 370; Berufsbildungssystem; Duales System; Typologie; Transfer; Bildungstransfer; Internationale Zusammenarbeit; Spanien; Albanien; Bundesrepublik Deutschland